Synthesis, physical-chemical and biological properties of derivatives of 3-methyl-7-ethylxanthinyl-8-thioacetic acid hydrazide - M. I. Romanenko; O. P. Dolhikh; D. H. Ivanchenko; K. V. Aleksandrova; N. M. Polishchuk (Zaporozhye State Medical University, 2018)
A wide range of biological activity of natural xanthines stimulated the search of biologically active compounds among their synthetic analogues, which led to the creation of a number of medicines (Nihexynum, Proxyphyllinum, Protheobrominum, etc.), which have been successfully applied till present time. It should be noted that the search of new biologically active compounds among xanthine derivatives does not stop. Previously, we had found that xanthine thioderivatives exhibits antioxidant, diuretic, hypoglycemic, antitumor, antimicrobial, anti-inflammatory, analgesic activity. The aim of the work is to elaborate simple laboratory methods of 7-ethyl-3-methylxanthine derivatives synthesis, unspecified in scientific papers earlier, - the basis for the creation of original antimicrobial and antifungal medicines. Materials and methods of research. The melting point has been determined with the help of an open capillary method with PTP-M device. Elemental analysis has been performed with the help of the instrument Elementar Vario L cube, NMR-spectra have been taken on a spectrometer Bruker SF-400 (operating frequency of 400 MHz, solvent DMSO, internal standard - TMS). Study of antimicrobial and antifungal activity of synthesized compounds has been performed by a two-fold serial dilution method. Standard test strains have been used for the study: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Candida albicans ATCC 885-653. Dimethylsulfoxide was used as the solvent of the compounds. Results and their discussion. Under short-time heating up of 7-ethyl-3-methyl-8-thioxanthine with methyl chloroacetate in a water-ethanol solution of sodium hydroxide leads to the formation of the corresponding ester. 3-Methyl-7-ethylxanthinyl-8-thioacethydrazide was obtained by hydrazinolysis of methyl(3-methyl-7-ethylxanthinyl-8-)thioacetate. Corresponding 7-ethyl-3-methylxanthinyl-8-thioacetic acid benzylidene hydrazides were obtained by the reaction of hydrazide with aromatic aldehydes. Structure of synthesized compounds was definitely proved by NMR-spectroscopy. Conducting primary screening research of antimicrobial activity of 8-thioderivatives of 7-ethyl-3-methylxanthine, which revealed moderate and weak activity in concentrations 50-100 mcg/ml. 2-Methoxy-5-bromobenzylidenehydrazide showed a pronounced antifungal effect. Conclusions. The preparative method of synthesis of 7-ethyl-3-methylxanthinyl-8-thioacetic acid benzylidene hydrazides, unspecified in scientific papers earlier, was developed. The structure of the synthesized compounds and their existence in the form of a mixture of E- and Z-isomers in the ratio 2:1 was proved with the help of the NMR spectroscopy data. The antimicrobial and antifungal effects of the obtained compounds were studied. Priorities for further research of biologically active compounds have been outlined.